If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 = 8 + -1(z + 10) Reorder the terms: 15 = 8 + -1(10 + z) 15 = 8 + (10 * -1 + z * -1) 15 = 8 + (-10 + -1z) Combine like terms: 8 + -10 = -2 15 = -2 + -1z Solving 15 = -2 + -1z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add 'z' to each side of the equation. 15 + z = -2 + -1z + z Combine like terms: -1z + z = 0 15 + z = -2 + 0 15 + z = -2 Add '-15' to each side of the equation. 15 + -15 + z = -2 + -15 Combine like terms: 15 + -15 = 0 0 + z = -2 + -15 z = -2 + -15 Combine like terms: -2 + -15 = -17 z = -17 Simplifying z = -17
| 42/4a=4 | | 3m-2/3=211/3 | | 6x-1=11+5 | | X-3=3+3x | | 4/5p=3 | | -5(3+r)=30 | | -6.8+4.24=x | | y=1/3x1-2 | | 6(x+3)+8=-16 | | 28x+x+25*32= | | 3t-14t-4=18 | | (3x+5)(2x-1)=x(6x+1)-16 | | x=40.8 | | 20x-7=5+17x | | 7+2p=x | | 7+2p= | | xy+18=32 | | 8x-16=12x+32 | | 28x+x+25= | | 7x+3(4x-13)=189 | | 28x+x= | | 0.11x+0.12(900-x)=100 | | x+4y=23 | | 3x^3-21x^2-24x=0 | | x+3=-6x+3-6x | | Z^2-4iz-3=0 | | .35x+.50y=29 | | 2/5y-5=11 | | 3x^3+6x^2+24=0 | | 2x-22=6(x+3) | | m-41=x | | 1/2(8-c) |